Enhancing motor performance in the healthy and Parkinsonian brain: adaptation, oscillations, and electrical stimulation - Joundi, RA (2012)
Parkinson's disease (PD) is characterized by debilitating impairments in motor control arising from pathophysiological alterations in basal ganglia circuitry and function. In this research thesis two main approaches, namely electrical recording and stimulation, are combined in order to better understand motor performance in Parkinson's disease and ways it might be improved. Three main types of motor behaviors are studied: discrete ballistic movement, repetitive movement, and motor adaptation. First, deep brain stimulation (DBS) of the subthalamic nucleus (STN) was shown to improve the velocity of discrete, ballistic movements in PD. The neural correlates of ballistic movements were then studied by recording from the STN of PD patients, revealing onset of beta-range desynchronization prior to, and gamma-range frequency synchronization during, performance of fast arm reaches. To determine a causal role for these oscillatory frequencies in motor behavior, the motor cortex of healthy humans was stimulated at either beta or gamma frequency during a 'go/no-go' grip force task. Beta stimulation resulted in slower force generation on 'go' trials but enhanced inhibition during 'no-go' trials, whereas gamma stimulation resulted in faster force generation on 'go' trials. Second, STN DBS resulted in improved repetitive tapping performance in PD patients through a reduction in variability. Recordings from the STN demonstrated that repetitive movement was accompanied by a substantial and persistent suppression of beta oscillatory activity. Third, Parkinson's patients were tested on a motor adaptation task, revealing intact learning but impaired retention of a visuomotor rotation. Application of direct current stimulation of the motor cortex resulted in enhanced adaptation during both learning and retention in PD patients and healthy controls. These results causally implicate the basal ganglia and oscillatory activity in motor control, provide insight into the neuronal mechanisms of motor performance and adaptation, and demonstrate promising new avenues for enhancing motor control in Parkinson's disease.